Pouring sealant with high thermal conductivity
The core-shell structure Al2O3@Al was prepared by high-temperature calcining aluminum powder, and combined with thermal conductivity and flame retardant fillers, a high-thermal conductivity potting adhesive was prepared, which solved the problem of insufficient thermal conductivity of existing epoxy resin potting adhesives and achieved efficient thermal conductivity and flame retardant performance improves.
Patent Information
- Application Number
- CN202411562332.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The existing epoxy resin potting glue has low thermal conductivity, making it difficult to meet the temperature stability requirements after the heating capacity of new energy vehicle motors increases.
Core-shell structure Al2O3@Al is prepared by calcining aluminum powder at high temperature, and aluminum powder is modified with silane coupling agent, combined with thermally conductive fillers such as silicon carbide powder and diamond powder, flame retardant fillers such as alumina and magnesium hydroxide, epoxy resin, curing High thermal conductivity potting adhesive is prepared by using agent, defoaming agent and anti-deposition agent.
The thermal conductivity and flame retardant properties of high thermal conductivity potting adhesives are improved, which can effectively reduce the motor temperature and improve the stability and service life of the motor.
Smart Images

Figure BDA0005118210890000101 
Figure BDA0005118210890000111 
Figure BDA0005118210890000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a high thermal conductivity potting glue. Background Art
[0002] New energy vehicles are composed of batteries, motors and energy conversion systems, among which the motor is one of its key components. The stable operation of the motor is directly related to the safety, riding comfort and service life of the vehicle. Potting glue is often used in motors for potting protection. Potting glue is a liquid polyurethane compound that is mechanically or manually poured into devices equipped with electronic components and circuits, and solidified at room temperature or heating conditions to become a thermosetting polymer insulating material with excellent performance. The liquid polyurethane compound used in this process is potting glue.
[0003] In terms of material type, there are three main types of potting glues that are used the most, namely epoxy resin potting glue, silicone resin potting glue, and polyurethane potting glue. Among them, epoxy potting glue has excellent insulation, weather resistance, adhesion and sealing properties. However, the thermal conductivity of epoxy potting glue is relatively low, usually about 0.2W·m-1·K-1. In order to improve the thermal conductivity of the potting glue, it is often achieved by adding high thermal conductivity fillers. The thermal conductivity of metal fillers is relatively high. For example, the thermal conductivity of aluminum is 237W·m-1·K-1. Filling metal fillers in the potting glue can significantly improve its thermal conductivity. However, the conductivity of metal fillers will cause the insulation performance of the potting glue to decrease. Compared with metal fillers, inorganic fillers have lower thermal conductivity, and the thermal conductivity of potting glue filled with inorganic fillers is also lower.
[0004] As motors develop towards miniaturization and high power, their heat generation increases significantly. The increase in motor temperature will have an adverse effect on the stability of the motor. Therefore, the potting compound not only needs to have excellent insulation properties, but also needs to have excellent thermal conductivity and flame retardant properties. In the prior art, for example, patent technology document CN111944469B discloses a highly flame-retardant epoxy resin potting compound, its preparation method and application. The invention includes component A and component B. Component A includes: polypropylene glycol diglycidyl ether, bisphenol A epoxy resin, trifunctional epoxy diluent, graphene oxide, fumed silica, α-alumina powder, crystalline silicon powder; component B includes: tertiary amine curing agent, silicone modified polyether amine, first polyether amine. By compounding the components, a potting compound with good flame retardant properties is prepared, but its thermal conductivity needs to be further improved.
[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a high thermal conductivity potting glue. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a high thermal conductivity potting glue to solve the problem of poor thermal conductivity of epoxy resin potting glue in the prior art.
[0007] Based on the above purpose, the present invention provides a high thermal conductivity potting glue.
[0008] A high thermal conductivity potting glue is prepared from the following raw materials in parts by weight:
[0009] Modified aluminum powder 20-50 parts, silicon carbide powder 10-20 parts, diamond powder 1-3 parts, four-needle zinc oxide whisker 1-3 parts, aluminum oxide powder 10-20 parts, calcium hydroxide powder 1-5 parts, magnesium hydroxide powder 1-5 parts, epoxy resin 30-45 parts, curing agent 9-13.5 parts, defoaming agent 0.1-1 parts, anti-settling agent 0.1-1 parts;
[0010] The modified aluminum powder is prepared from a silane coupling agent and aluminum powder.
[0011] Preferably, the preparation method of the modified aluminum powder is as follows:
[0012] Step A1. Wash aluminum powder twice with anhydrous ethanol and once with deionized water, dry it in vacuum at 60-70°C for 2-3h, and then calcine the dried aluminum powder in a muffle furnace at high temperature to obtain a core-shell structure Al2O3@Al, wherein Al2O3 is the shell and Al is the core;
[0013] Step A2. Add silane coupling agent to a flask containing deionized water, stir evenly, then add Al2O3@Al, heat to reflux, wash twice with deionized water, and dry at 35-45°C for 3-4 hours to obtain modified aluminum powder.
[0014] Preferably, the aluminum powder in step A1 has a particle size of 0.1-1.5 mm;
[0015] The heating rate during high-temperature calcination is 3-5°C / min, the temperature is raised to 400-480°C, and the calcination time is 6-8h.
[0016] Preferably, the mass ratio of deionized water, silane coupling agent and Al2O3@Al in step A2 is 12-16:0.2-0.56:20-28;
[0017] The silane coupling agent is any one of 3-glycidyloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
[0018] Preferably, the temperature during heating and reflux in step A2 is 70-80° C., and the reflux time is 90-120 min.
[0019] Preferably, the particle size of the aluminum oxide is 50 μm-80 μm;
[0020] The particle size of the silicon carbide powder is 1-5 μm;
[0021] The particle size of the diamond powder is 20-50 μm;
[0022] The particle size of the aluminum hydroxide powder is 60-80 μm;
[0023] The particle size of the magnesium hydroxide powder is 60-80 μm;
[0024] The epoxy resin is epoxy resin 135;
[0025] The curing agent is obtained by mixing methyltetrahydrophthalic anhydride and hexahydrophthalic anhydride in a mass ratio of 2-4:1.
[0026] Preferably, the anti-settling agent is any one of DK-063, DK-149, DK-006 and DK-045;
[0027] The defoaming agent is silicone defoaming agent 1410.
[0028] Preferably, the preparation method of the high thermal conductivity potting glue is as follows:
[0029] Step S1. Add modified aluminum powder and silicon carbide powder, diamond powder, aluminum oxide powder, four-needle zinc oxide whisker, calcium hydroxide powder, magnesium hydroxide powder, epoxy resin, curing agent, defoaming agent and anti-settling agent into a beaker, mix well and place in a vacuum drying oven for degassing to obtain a liquid potting glue;
[0030] Step S2. Pour the liquid potting glue into the mold, place it at room temperature for 50-70 minutes, place it in an oven for heating and curing for 4.5-5.5 hours, and then heat it for 1.5-2.5 hours to obtain a high thermal conductivity potting glue.
[0031] Preferably, the absolute vacuum degree during the degassing treatment in step S1 is 50-200 mbar, and the degassing time is 18-28 min.
[0032] Preferably, the temperature during heating and curing in step S2 is 65-75°C, and the temperature during heating is 110-120°C.
[0033] Beneficial effects of the present invention:
[0034] The invention provides a high thermal conductivity potting glue. The invention obtains a core-shell structure Al2O3@Al with Al2O3 as a shell and Al as a core by calcining aluminum powder at a high temperature, and then modifies the aluminum powder with a silane coupling agent to obtain a modified aluminum powder. The modified aluminum powder is then mixed with a thermal conductive filler, a flame retardant filler, an epoxy resin, a curing agent, a defoaming agent and an anti-settling agent to obtain a high thermal conductivity potting glue. The high thermal conductivity potting glue prepared by the invention has good thermal conductivity and good flame retardancy.
[0035] Among them, the core-shell structure Al2O3@Al composite material has an alumina shell that makes the composite material have good insulation properties, and the aluminum metal in its core has good thermal conductivity, and the silane coupling agent modified Al2O3@Al can enhance its compatibility in epoxy resin; the thermal conductive filler used is a one-dimensional structure with high thermal conductivity of silicon carbide powder and high thermal conductivity of diamond powder, which is beneficial to strengthen the heat transfer of the potting glue; the three-dimensional four-needle stereoscopic structure of zinc oxide whiskers is beneficial to improve the structural performance of the potting glue, and various raw materials work together to make the potting glue prepared in the present invention have good thermal conductivity and flame retardant properties, and the raw materials used in the present invention are easy to obtain, the production process is simple, and compared with the prior art, it has broad application prospects. DETAILED DESCRIPTION
[0036] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0037] The sources and properties of some of the raw materials used in the present invention are as follows:
[0038] Aluminum powder was purchased from Harbin Dongqing Metal Material Processing Co., Ltd.; epoxy resin 135 was purchased from Langfang Anhong Environmental Protection Technology Co., Ltd.; silicon carbide powder was purchased from Xi'an Bor New Materials Co., Ltd.; diamond micropowder was purchased from Huifeng Diamond Co., Ltd.; and four-needle zinc oxide whiskers were purchased from Chengdu Tianyou Jingchuang Technology Co., Ltd.
[0039] Embodiment 1: A method for preparing a high thermal conductivity potting compound, comprising the following steps:
[0040] S1. Wash the aluminum powder through a 140-mesh sieve twice with anhydrous ethanol and once with deionized water, and dry it under vacuum at 60°C for 3 h. Then, place the dried aluminum powder in a muffle furnace, set the heating rate at 3°C / min, heat it to 400°C and calcine it for 8 h to obtain a core-shell structure Al2O3@Al;
[0041] S2. Add 0.2 g of γ-aminopropyltriethoxysilane to a flask containing 12 g of deionized water, stir evenly, then add 20 g of Al2O3@Al, heat and reflux at 70°C for 120 min, wash twice with deionized water, and dry at 35°C for 4 h to obtain modified aluminum powder;
[0042] S3. 20g of modified aluminum powder and 10g of silicon carbide powder through a 2500 mesh sieve, 1g of diamond powder through a 500 mesh sieve, 10g of alumina powder through a 200 mesh sieve, 1g of four-needle zinc oxide whisker, 1g of calcium hydroxide powder through a 245 mesh sieve, 1g of magnesium hydroxide powder through a 245 mesh sieve, 30g of epoxy resin 135, 9g of curing agent, 0.1g of silicone defoamer 1410 and 0.1gDK-063 were added to a beaker, wherein the curing agent was obtained by mixing 2g of methyltetrahydrophthalic anhydride and 1g of hexahydrophthalic anhydride, mixed evenly and placed in a vacuum drying oven for degassing, and the absolute vacuum degree was set to 50mbar, the degassing time was 18min, and a liquid potting glue was obtained;
[0043] S4. Pour the liquid potting glue into the mold, place it at room temperature for 50 minutes, place it in an oven and heat it at 65°C for 5.5 hours, then heat it to 110°C and heat it for 2.5 hours to obtain a high thermal conductivity potting glue.
[0044] Embodiment 2: A method for preparing a high thermal conductivity potting adhesive, comprising the following steps:
[0045] S1. Wash the aluminum powder through a 45-mesh sieve twice with anhydrous ethanol and once with deionized water, and dry it under vacuum at 63°C for 2.5 h. Then, place the dried aluminum powder in a muffle furnace, set the heating rate to 4°C / min, heat it to 430°C and calcine it for 7.5 h to obtain a core-shell structure Al2O3@Al;
[0046] S2. Add 0.3 g of γ-aminopropyltriethoxysilane to a flask containing 14 g of deionized water, stir evenly, then add 24 g of Al2O3@Al, heat and reflux at 73 ° C for 110 min, wash twice with deionized water, and dry at 38 ° C for 3.5 h to obtain modified aluminum powder;
[0047] S3. 30g of modified aluminum powder and 13g of silicon carbide powder through a 2500 mesh sieve, 2g of diamond powder through a 625 mesh sieve, 13g of alumina powder through a 250 mesh sieve, 2g of four-needle zinc oxide whiskers, 2g of calcium hydroxide powder through a 220 mesh sieve, 2g of magnesium hydroxide powder through a 220 mesh sieve, 35g of epoxy resin 135, 10.5g of curing agent, 0.4g of silicone defoamer 1410 and 0.4g of DK-063 were added to a beaker, wherein the curing agent was obtained by mixing 3g of methyltetrahydrophthalic anhydride and 1g of hexahydrophthalic anhydride, mixed evenly and placed in a vacuum drying oven for degassing, and the absolute vacuum degree was set to 100mbar, the degassing time was 21min, and a liquid potting glue was obtained;
[0048] S4. Pour the liquid potting compound into the mold, place it at room temperature for 60 minutes, heat it in an oven at 68°C for 5 hours, and then heat it to 113°C for 2 hours to obtain a high thermal conductivity potting compound.
[0049] Embodiment 3: A method for preparing a high thermal conductivity potting adhesive, comprising the following steps:
[0050] S1. Wash the aluminum powder through a 25-mesh sieve twice with anhydrous ethanol and once with deionized water, and dry it under vacuum at 67°C for 2.5 h. Then, place the dried aluminum powder in a muffle furnace, set the heating rate to 4°C / min, and heat it to 460°C for calcination for 7 h to obtain a core-shell structure Al2O3@Al;
[0051] S2. Add 0.4 g of γ-aminopropyltriethoxysilane to a flask containing 15 g of deionized water, stir evenly, then add 26 g of Al2O3@Al, heat and reflux at 77°C for 100 min, wash twice with deionized water, and dry at 42°C for 3.5 h to obtain modified aluminum powder;
[0052] S3. 40g of modified aluminum powder and 17g of silicon carbide powder through a 2500 mesh sieve, 2g of diamond powder through a 425 mesh sieve, 17g of alumina powder through a 250 mesh sieve, 2g of four-needle zinc oxide whiskers, 3g of calcium hydroxide powder through a 220 mesh sieve, 3g of magnesium hydroxide powder through a 220 mesh sieve, 40g of epoxy resin 135, 12g of curing agent, 0.7g of silicone defoamer 1410 and 0.7gDK-063 were added to a beaker, wherein the curing agent was obtained by mixing 3g of methyltetrahydrophthalic anhydride and 1g of hexahydrophthalic anhydride, mixed evenly and placed in a vacuum drying oven for degassing, and the absolute vacuum degree was set to 150mbar, the degassing time was 25min, and a liquid potting glue was obtained;
[0053] S4. Pour the liquid potting compound into the mold, place it at room temperature for 65 minutes, place it in an oven and heat it at 71°C for 5 hours, then heat it to 117°C for 2 hours to obtain a high thermal conductivity potting compound.
[0054] Embodiment 4: A method for preparing a high thermal conductivity potting adhesive, comprising the following steps:
[0055] S1. Wash the aluminum powder through a 12-mesh sieve twice with anhydrous ethanol and once with deionized water, dry it in a vacuum oven at 70°C for 2 h, and then place the dried aluminum powder in a muffle furnace at a heating rate of 5°C / min to 480°C for calcination for 8 h to obtain a core-shell structure Al2O3@Al;
[0056] S2. Add 0.56 g of γ-aminopropyltriethoxysilane to a flask containing 16 g of deionized water, stir evenly, then add 28 g of Al2O3@Al, heat and reflux at 80°C for 90 min, wash twice with deionized water, and dry at 45°C for 3 h to obtain modified aluminum powder;
[0057] S3. 50g of modified aluminum powder and 20g of silicon carbide powder through a 2500 mesh sieve, 3g of diamond powder through a 325 mesh sieve, 20g of alumina powder through a 270 mesh sieve, 3g of four-needle zinc oxide whiskers, 5g of calcium hydroxide powder through a 198 mesh sieve, 5g of magnesium hydroxide powder through a 198 mesh sieve, 45g of epoxy resin 135, 13.5g of curing agent, 1g of silicone defoamer 1410 and 1gDK-063 were added to a beaker, wherein the curing agent was obtained by mixing 4g of methyltetrahydrophthalic anhydride and 1g of hexahydrophthalic anhydride, mixed evenly and placed in a vacuum drying oven for degassing, and the absolute vacuum degree was set to 200mbar, the degassing time was 28min, and a liquid potting glue was obtained;
[0058] S4. Pour the liquid potting glue into the mold, place it at room temperature for 70 minutes, place it in an oven and heat it at 75°C for 5.5 hours, then heat it to 120°C and heat it for 2.5 hours to obtain a high thermal conductivity potting glue.
[0059] Comparative Example 1:
[0060] Compared with Example 1, this comparative example only replaces "modified aluminum powder" with "aluminum powder", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a high thermal conductive potting glue is obtained.
[0061] Comparative Example 2:
[0062] S1. Wash aluminum powder with a particle size of 0.1 mm twice with anhydrous ethanol and once with deionized water, place it in a vacuum dryer at 60°C for 3 h, and then place the dried aluminum powder in a muffle furnace, set the heating rate to 3°C / min, and heat it to 400°C for calcination for 8 h to obtain a core-shell structure Al2O3@Al;
[0063] S2. 20gAl2O3@Al and 10g silicon carbide powder, 1g diamond powder, 10g alumina powder with a particle size of 15μm, 1g tetrapod-shaped zinc oxide whisker, 1g calcium hydroxide powder, 1g magnesium hydroxide powder, 30g epoxy resin 135, 9g curing agent, 0.1g silicone defoamer 1410 and 0.1gDK-063 were added to a beaker, wherein the curing agent was obtained by mixing 2g methyltetrahydrophthalic anhydride and 1g hexahydrophthalic anhydride, and the mixture was evenly placed in a vacuum drying oven for degassing, and the absolute vacuum was set to 50mbar, and the degassing time was 18min to obtain a liquid potting glue;
[0064] S3. Pour the liquid potting glue into the mold, place it at room temperature for 50 minutes, place it in an oven and heat it at 65°C for 5.5 hours, then heat it to 110°C and heat it for 2.5 hours to obtain a high thermal conductivity potting glue.
[0065] Performance Test:
[0066] Thermal conductivity test:
[0067] Referring to ISO22007.2:2008 standard, a DRE-III automatic thermal conductivity tester was used to take out the high thermal conductivity potting glue prepared in Examples 1-4 and Comparative Examples 1-2 and cool it to room temperature, set the constant temperature water bath temperature to 25°C, wipe the lower thermal electrode with a dust-free cloth to prevent moisture, and respectively put the high thermal conductivity potting rings prepared in Examples 1-4 and Comparative Examples 1-2 on the steel ring of the lower fixture, put the potting glue standard sheet in, start the automatic testing system, and start testing the thermal conductivity of the potting glue;
[0068] Volume resistivity:
[0069] According to ASTM D257, the high thermal conductivity potting glue prepared in Examples 1-4 and Comparative Examples 1-2 were cooled to 20±5° C. after preheating, and the electrodes of a high resistance meter were connected to both ends of the high thermal conductivity potting glue. A test voltage was applied for 1 min, and the indicated resistance value was read.
[0070] The calculation formula of volume resistivity is:
[0071]
[0072] Where ρv is the volume resistivity, Rv is the resistance value, A is the effective area of the electrode, and d is the thickness of the high thermal conductivity potting compound.
[0073] Flame retardant performance test:
[0074] According to the UL-94 standard, the high thermal conductivity potting glue prepared in Examples 1-4 and Comparative Examples 1-2 were respectively suspended vertically in a vertical position, with 75 mm of the full length of the high thermal conductivity potting glue exposed at the upper 300 mm. Then, the bottom of the material was ignited, and the ignition source was a fixed flame with a flame height of 20 mm and a combustion temperature of 500° C. The performance of the high thermal conductivity potting glue during the combustion process was observed and evaluated based on the burning time, the remaining burning time, the number of falling flame drops, and the burning height parameters.
[0075] Assessment level:
[0076] V-0: The burning time of the sample does not exceed 10 seconds, the remaining burning time does not exceed 30 seconds, and there is no falling flame or dripping.
[0077] V-1: The burning time of the sample does not exceed 30 seconds, the remaining burning time does not exceed 60 seconds, and there is no falling flame or dripping.
[0078] V-2: The burning time of the sample does not exceed 30 seconds, and the remaining burning time does not exceed 60 seconds, but a small amount of falling flame is allowed.
[0079] One end of the 3mm high thermal conductivity potting glue prepared in Example 1-4 and Comparative Example 1-2 was clamped horizontally at 45 degrees to the horizontal, an iron mesh was taken and fixed horizontally 10±1mm below the high thermal conductivity potting glue, a Bunsen burner (flame height of about 20mm) was moved to 45 degrees to the other end of the test piece to contact 6mm of the high thermal conductivity potting glue, and the timer was moved away after 30 seconds. When the test piece burned to the 25mm mark, another timer was started. If it burned to the 25mm mark within 30 seconds, another timer was started and the Bunsen burner was moved away;
[0080] Assessment level:
[0081] When the sample thickness is 12.7mm, the burning speed on the 76.2mm gauge length shall not exceed 38.1mm / min; when the sample thickness is less than 3.05mm, the burning speed shall not exceed 38.1mm / min or the burning shall stop before reaching the 102mm mark.
[0082] Tensile Strength:
[0083] With reference to GB / T1040.1-2006 standard, the tensile strength of the high thermal conductive potting adhesives prepared in Examples 1-4 and Comparative Examples 1-2 was measured using a universal tensile testing machine.
[0084] Table 1
[0085]
[0086]
[0087] Data Analysis:
[0088] As can be seen from Table 1, the high thermal conductivity potting glue prepared by the present invention has better thermal conductivity and flame retardant properties. This may be because the high-temperature calcination of aluminum powder obtains the core-shell structure Al2O3@Al with Al2O3 as the shell and Al as the core, and the silane coupling agent can effectively reduce the polarity of the Al2O3 surface and enhance its compatibility with the epoxy resin, thereby forming a closer contact in the filling material, reducing the interface thermal resistance, and improving the overall thermal conductivity efficiency of the potting glue. It synergizes with aluminum oxide, four-needle zinc oxide whiskers and diamond powder thermal conductive fillers, and aluminum hydroxide and magnesium hydroxide flame retardants can form a protective layer on the surface of the material, thereby playing a flame retardant role, so that the high thermal conductivity potting glue prepared by the present invention has good thermal conductivity and flame retardant properties;
[0089] As for Comparative Example 1, since "modified aluminum powder" is replaced by "aluminum powder", it can be seen from Table 1 that its thermal conductivity and flame retardancy are poor. This may be because the high-temperature calcination of aluminum powder obtains a core-shell structure Al2O3@Al with Al2O3 as the shell and Al as the core, and the silane coupling agent can effectively reduce the polarity of the Al2O3 surface and enhance its compatibility with the epoxy resin, thereby forming a closer contact in the filling material, reducing the interface thermal resistance, and improving the overall thermal conductivity and flame retardancy of the potting glue. Aluminum powder as an inorganic filler in epoxy resin The compatibility in the resin is poor, therefore, the thermal conductivity and flame retardancy of Comparative Example 1 are worse than those of Example 1; since the "modified aluminum powder" is replaced by "Al2O3@Al" in Comparative Example 2, it can be seen from Table 1 that its thermal conductivity and flame retardancy are poor, which may be because the silane coupling agent can effectively connect Al2O3 with the epoxy resin, improve the dispersibility of the inorganic filler in the resin, improve the interface bonding, and thus improve the overall thermal conductivity and flame retardancy of the potting glue. Therefore, the thermal conductivity and flame retardancy of Comparative Example 2 are worse than those of Example 1.
[0090] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0091] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high thermal conductivity potting glue, characterized in that: Prepared from the following raw materials in parts by weight: Modified aluminum powder 20-50 parts, silicon carbide powder 10-20 parts, diamond powder 1-3 parts, four-needle zinc oxide whisker 1-3 parts, aluminum oxide powder 10-20 parts, calcium hydroxide powder 1-5 parts, magnesium hydroxide powder 1-5 parts, epoxy resin 30-45 parts, curing agent 9-13.5 parts, defoaming agent 0.1-1 parts, anti-settling agent 0.1-1 parts; The modified aluminum powder is prepared from a silane coupling agent and aluminum powder.
2. The high thermal conductivity potting adhesive according to claim 1, characterized in that: The preparation method of the modified aluminum powder is as follows: Step A1. Wash the aluminum powder twice with anhydrous ethanol and once with deionized water, dry it in a vacuum at 60-70°C for 2-3h, and then calcine the dried aluminum powder in a muffle furnace at high temperature to obtain a core-shell structure Al2O3@Al; Step A2. Add silane coupling agent to a flask containing deionized water, stir evenly, then add Al2O3@Al, heat to reflux, wash twice with deionized water, and dry at 35-45°C for 3-4 hours to obtain modified aluminum powder.
3. The high thermal conductivity potting adhesive according to claim 2, characterized in that: The aluminum powder in step A1 has a particle size of 0.1-1.5 mm; The heating rate during high-temperature calcination is 3-5°C / min, the temperature is raised to 400-480°C, and the calcination time is 6-8h.
4. The high thermal conductivity potting adhesive according to claim 2, characterized in that: The mass ratio of deionized water, silane coupling agent and Al2O3@Al in step A2 is 12-16: 0.2-0.56: 20-28; The silane coupling agent is any one of 3-glycidyloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
5. The high thermal conductivity potting adhesive according to claim 2, characterized in that: The temperature during heating and reflux in step A2 is 70-80° C., and the reflux time is 90-120 min.
6. The high thermal conductivity potting adhesive according to claim 1, characterized in that: The particle size of the aluminum oxide is 50 μm-80 μm; The particle size of the silicon carbide powder is 1-5 μm; The particle size of the diamond powder is 20-50 μm; The particle size of the aluminum hydroxide powder is 60-80 μm; The particle size of the magnesium hydroxide powder is 60-80 μm; The epoxy resin is epoxy resin 135; The curing agent is obtained by mixing methyltetrahydrophthalic anhydride and hexahydrophthalic anhydride in a mass ratio of 2-4:
1.
7. The high thermal conductivity potting adhesive according to claim 1, characterized in that: The anti-settling agent is any one of DK-063, DK-149, DK-006 and DK-045; The defoaming agent is organic silicon defoaming agent 1410.
8. The high thermal conductivity potting adhesive according to claim 1, characterized in that: The preparation method of the high thermal conductivity potting glue is as follows: Step S1. Add modified aluminum powder and silicon carbide powder, diamond powder, aluminum oxide powder, four-needle zinc oxide whisker, calcium hydroxide powder, magnesium hydroxide powder, epoxy resin, curing agent, defoaming agent and anti-settling agent into a beaker, mix well and place in a vacuum drying oven for degassing to obtain a liquid potting glue; Step S2. Pour the liquid potting glue into the mold, place it at room temperature for 50-70 minutes, place it in an oven for heating and curing for 4.5-5.5 hours, and then heat it for 1.5-2.5 hours to obtain a high thermal conductivity potting glue.
9. The high thermal conductivity potting adhesive according to claim 8, characterized in that: The absolute vacuum degree during the degassing treatment in step S1 is 50-200 mbar, and the degassing time is 18-28 min.
10. The high thermal conductivity potting adhesive according to claim 8, characterized in that: The temperature during heating and curing in step S2 is 65-75°C, and the temperature during heating is 110-120°C.
Citation Information
Patent Citations
A high flame-retardant epoxy resin potting compound, its preparation method and application
CN111944469B
Cited By
An epoxy resin composition
CN122668509A